Relationship between Household Members with WTP for JKN in Balikpapan - Ardhiputri, Titania; Anggraeni, Ike; W Wisnuwardani, Ratih (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Universal Health Coverage (UHC) in Indonesia. In 2022, East Kalimantan was designated as the new capital, Nusantara, under Law No.3. Various regions in East Kalimantan show diverse participation rates in the PBPU (Non-Wage Recipient Benefit) program: Jakarta (18.5%), East Kalimantan (28.2%), PPU (14.2%), Paser (19.6%), and Kutai Kartanegara (39.9%), with Balikpapan—known as the gateway to the future capital—at 24.6%. Objective : to examine the relationship between household size and willingness to pay (WTP) for BPJS Kesehatan in Balikpapan. Research Methods/ Implementation Methods : Cross-Sectional study Results : A significant association was found between household size and willingness to pay for BPJS Kesehatan, with a p-value=0.0001. Conclusion/Lesson Learned : A negative association was found between the number of household members and willingness to pay for BPJS Kesehatan among participants in Balikpapan, highlighting potential barriers to health coverage in larger households.